The Effectiveness of Implementing the Problem Based Learning Model with a Contextual Approach on Students’ Numeracy Literacy Skills - Sartika, Dewi; Angriani, Andi Dian; Tayeb, Thamrin; Nursalam, Nursalam; Mattoliang, Lisnasari Andi (Faculty of Teacher Training and Education, 2026)
This study is motivated by students’ limited numeracy literacy skills, particularly in processing information, solving contextual problems, and evaluating mathematical results. It aims to explore the effects of integrating a Problem-Based Learning model with a contextual method on students’ literacy and numeracy skills. A nonequivalent pretest–posttest control group design employing a quasi-experimental method was utilized. The population consisted of all eighth-grade students at SMP Negeri 3 Pattallassang (State Junior High School 3 Pattallassang). The sample comprised class VIII.3 as the experimental group and class VIII.2 as the control group, selected using a random sampling technique. Data were collected through observation forms and a numeracy literacy test and were subsequently examined using descriptive and inferential statistics, including normality tests, homogeneity tests, and an independent-samples t-test. The results showed that students’ numeracy literacy skills taught using the direct instruction model were at a moderate level, whereas those taught using the problem-based learning model with a contextual approach were at a high level. This indicates a difference in the mean learning outcomes between the two groups. Furthermore, the relative efficiency analysis revealed that the problem-based learning model with a contextual approach was effective in improving the numeracy literacy skills of eighth-grade students at SMP Negeri 3 Pattallassang.